2016
DOI: 10.1080/00218464.2015.1116984
|View full text |Cite
|
Sign up to set email alerts
|

Failure analysis of adhesive-patch-repaired edge-notched composite plates

Abstract: In this study, it was achieved failure analysis of wet-patch-repaired composite plates, experimentally. U notched composite plates were repaired with wet patch and then static tensile load was applied to composite plates. The patch thickness, single and double patch repair and fiber orientation angle of composite plates effect on the failure load were investigated. The composite plates having eight plies woven glass fiber and epoxy matrix resin, woven glass fiber and epoxy based adhesive were used as materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
6
0
2
Order By: Relevance
“…Two carbon ber types were addressed, namely HM and HS. The patches are bonded using the Adekit A-140 adhesive, a widely used two-component epoxy adhesive in aviation due to its performance in terms of its multipurpose use in bonded assemblies and good mechanical properties, especially for composites, metals, and wood [19]. The repaired structures dimensions are presented in Table 1.…”
Section: -Geometric Model and Mechanical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Two carbon ber types were addressed, namely HM and HS. The patches are bonded using the Adekit A-140 adhesive, a widely used two-component epoxy adhesive in aviation due to its performance in terms of its multipurpose use in bonded assemblies and good mechanical properties, especially for composites, metals, and wood [19]. The repaired structures dimensions are presented in Table 1.…”
Section: -Geometric Model and Mechanical Propertiesmentioning
confidence: 99%
“…Composite repair has been shown to be an effective and cost effective method of extending the life of cracked components in the structure [16] [17]. Patch repairing can prevent or delay crack restart or crack propagation [18] [19]. These authors also showed that reducing the stress intensity factor can improve fatigue crack life by 30%.…”
mentioning
confidence: 99%
“…Hashin hasar kriteri deneysel sonuçlarla uyumlu bir şekilde kullanılmaktadır. Ayrıca bu kriterin farklı kriterlerle karşılaştırması yapılmakta (Duarte vd., 2017) ve modifikasyonları geliştirilmektedir (Gu ve Chen, 2017 (Turan vd., 2015;Turan ve Orcen, 2017). Bu çalışmada ise, çekme yükü etkisindeki ortasında dairesel delik bulunan kompozit levhada sayısal nihai hasar değeri, çekme testlerinde olduğu gibi kırılma sonucu maksimum reaksiyon kuvvetinin düşmeye başladığı nokta kontrol edilerek belirlenmiştir.…”
Section: Kompozit Malzemelerin Hasar Davranışındaunclassified
“…Kompozitler için ara yüzey eleman (interface element) (Bai vd., 2017;Riccio vd., 2017) ve ilerlemeli hasar (progressive failure) (Liu vd., 2014;Warren, vd., 2016) teknikleri güncel metotlar arasındadır. Ara yüzey eleman modelinde hasar bölgesi çalışma öncesinde belirlenmektedir ve maksimum hasar gerilmesinin aşıldığı durumlarda ilgili yüzeylerde kompozitin tabakaları arasında ayrılma (delamination) hasarının oluşması sağlanır (Yang vd., 2017 (Turan vd., 2015;Turan ve Orcen, 2017). Bu çalışmada ise, çekme yükü etkisindeki ortasında dairesel delik bulunan kompozit levhada sayısal nihai hasar değeri, çekme testlerinde olduğu gibi kırılma sonucu maksimum reaksiyon kuvvetinin düşmeye başladığı nokta kontrol edilerek belirlenmiştir.…”
Section: öZunclassified
“…Therefore, in recent years, considerable experimental and numerical studies have been conducted to investigate the influence of different repair parameters on the stress distributions, ultimate strength and stress intensity factor of the bonded repaired structures [1]. A number of authors [1][2][3][4][5][6][7][8][9]11,16] have studied the analysis of failure mechanism of the bonded patch repair in laminated composite materials. Wisnom M.R.…”
Section: Introductionmentioning
confidence: 99%